Investigating the Role of Using Electronic Health Record (EHR) in Physician-Patient Relationship: A Qualitative Study - Aref Shayganmehr; Gholamreza Malekzade; Mariusz Trojanowski (Kerman University of Medical Sciences, 2022)
Introduction: Electronic Health Record (EHR) is an opportunity to implement healthcare services remotely especially in situations that social distance is necessary, such as in Covid-19 pandemic. The relationship between physician and patient is very important in medicine and it has been described as a basic axis of clinical measures and the foundation stone of proper activities in the health system. However, one of the main factors less considered in the design and deployment of health technologies is the physician-patient relationship, emotions, and feelings. The present study aimed to investigate the role of using electronic health records on physician-patient relationship. Methods: In this study, qualitative data collection was carried out via unstructured and semi-structured interviews and focus group discussion, using a phenomenological approach. A thematic analysis approach was also used to analyze the transcripts. A total of 24 participants, including eight physicians, three specialists (pediatricians, gynecologists, and psychiatrists), four psychologists, five health care providers, and four chief executive officers were selected using purposive sampling. Results: The results of this study revealed using EHR could influence interpersonal communication as well as empathetic and sympathetic relationship between physician and patient. The relevant classes are explained in detail in the main text of the article. Conclusion: While EHR is beneficial, the concerns overshadowing the interactions between physician and patient cause users to change their perception of the benefits and efficiency of EHR.